(untitled) (Marketing Journal, 2025)
The article examines the factors influencing the improvement of the transport system of the Khorezm region. The level of influence of the transport system on the socio -economic development of the region is studied, and scientific proposals and recommendati ons for the development of transport services in the region are developed.